Another Look at the Acceptability of Bare Singular NPs in Episodic Sentences in Brazilian Portuguese. (11th October 2018) - Ionin, Tania; Grolla, Elaine; Santos, Hélade
Abstract: Bare (determinerless) singular NPs in Brazilian Portuguese have been variously analyzed as indefinite terms, as kind terms, or as ambiguous between the two. It has furthermore been noted (Schmitt & Munn1999 and subsequent literature) that bare singulars, unlike bare plurals, are degraded in the preverbal subject position of episodic sentences but that their acceptability is improved when they are embedded in a list. We conducted an experimental study examining the effects of NP type, syntactic position, and list context on the acceptability of bare NPs in Brazilian Portuguese. Our results indicate that the low acceptability of bare singulars in the subject position of episodic sentences results from the additive effects of three separate factors, rather than from a constraint against bare singulars in subject position. Implications of these findings for theories of bare‐NP interpretation in Brazilian Portuguese are discussed.